Characterization of the Lytic Capability of a LysK-Like Endolysin, Lys-phiSA012, Derived from a Polyvalent Staphylococcus aureus Bacteriophage - Jumpei Fujiki; Tomohiro Nakamura; Takaaki Furusawa; Hazuki Ohno; Hiromichi Takahashi; Junya Kitana; Masaru Usui; Hidetoshi Higuchi; Yasunori Tanji; Yutaka Tamura; Hidetomo Iwano (MDPI AG, 2018)
Antibiotic-resistant bacteria (ARB) have spread widely and rapidly, with their increased occurrence corresponding with the increased use of antibiotics. Infections caused by Staphylococcus aureus have a considerable negative impact on human and livestock health. Bacteriophages and their peptidoglycan hydrolytic enzymes (endolysins) have received significant attention as novel approaches against ARB, including S. aureus. In the present study, we purified an endolysin, Lys-phiSA012, which harbors a cysteine/histidine-dependent amidohydrolase/peptidase (CHAP) domain, an amidase domain, and a SH3b cell wall binding domain, derived from a polyvalent S. aureus bacteriophage which we reported previously. We demonstrate that Lys-phiSA012 exhibits high lytic activity towards staphylococcal strains, including methicillin-resistant S. aureus (MRSA). Analysis of deletion mutants showed that only mutants possessing the CHAP and SH3b domains could lyse S. aureus, indicating that lytic activity of the CHAP domain depended on the SH3b domain. The presence of at least 1 mM Ca2+ and 100 µM Zn2+ enhanced the lytic activity of Lys-phiSA012 in a turbidity reduction assay. Furthermore, a minimum inhibitory concentration (MIC) assay showed that the addition of Lys-phiSA012 decreased the MIC of oxacillin. Our results suggest that endolysins are a promising approach for replacing current antimicrobial agents and may contribute to the proper use of antibiotics, leading to the reduction of ARB.